Sustainable entrepreneurship education and training program in the context of Asian society to develop sustainable entrepreneurial students - Dadi; Dormido, Yasmin Pascual; Agustini, Rina; Ratnawati (Badan Kemitraan Inovasi dan Kewirausahaan Universitas Galuh, 2025)
The Sustainable Entrepreneurship Education and Training Program at Universitas Galuh is designed to enhance students' understanding of sustainable entrepreneurship, develop innovative skills, and foster positive entrepreneurial attitudes. The program was implemented intensively from September 2024 to February 2025, which engaged 150 students from 19 study programs and featured 17 expert speakers from various countries. The training methods incorporated lectures, case studies, and group discussions, emphasizing sustainable entrepreneurship's theoretical foundations and practical applications. A Likert-scale survey and qualitative feedback were utilized as evaluation instruments to assess the program's effectiveness. The results indicated a significant improvement in students' knowledge and comprehension, entrepreneurial innovation skills, attitudes, motivations, and high levels of participant satisfaction. Additionally, the program was perceived as highly relevant to the context of the Asian community. The dissemination and promotion of the program through social media and mass media further enhanced its visibility and strengthened the academic reputation of Universitas Galuh. The program successfully met its objective of preparing students to become sustainable entrepreneurs. This achievement was attributed to the well-structured curriculum, the expertise of invited speakers, interactive pedagogical approaches, and the materials' relevance. Given its success, this program has the potential to serve as a model for the development of future sustainable entrepreneurship education initiatives.